Job Loss and Employment Patterns of Older Workers - Chan, Sewin; Huff Stevens, Ann (Journal of Labor Economics, 2001)
This article uses data from the Health and Retirement Study to examine the employment patterns of workers aged 50 and above who have experienced an involuntary job loss. Hazard models for returning to work and for exiting postdisplacement employment are estimated and used to examine work patterns for 10 years following a job loss. Our findings show that a job loss results in large and lasting effects on future employment probabilities. Four years after job losses at age 55, the employment rate of displaced workers remains 20 percentage points below the employment rate of similar nondisplaced workers.